Inequalities in hip fracture incidence are greatest in the North of England: regional analysis of the effects of social deprivation on hip fracture incidence across England. (September 2018) - Bhimjiyani, A.; Neuburger, J.; Jones, T.; Ben-Shlomo, Y.; Gregson, C.L.
Abstract: Objectives: Hip fracture risk varies by geography and by levels of deprivation. We examined the effect of local area-level deprivation on hip fracture incidence across nine regions in England, using 14 years of hospital data, to determine whether inequalities in hip fracture incidence rates vary across geographic regions in England. Study design: Sequential annual cross-sectional studies over 14 years. Methods: We used English Hospital Episodes Statistics (2001/02–2014/15) to identify hip fractures in adults aged 50+ years and mid-year population estimates (2001–2014) from the Office for National Statistics. The Index of Multiple Deprivation was used to measure local area deprivation. We calculated age-standardised hip fracture incidence rates per 100, 000 population, stratified by gender, geographic region, deprivation quintiles and time-period, using the 2001 English population as the reference population. Using Poisson regression, we calculated age-adjusted incidence rate ratios (IRRs) for hip fracture, stratified as above. Results: Over 14 years, we identified 747, 369 hospital admissions with an index hip fracture. Age-standardised hip fracture incidence was highest in the North East for both men and women. In North England (North East, North West and Yorkshire and the Humber), hip fracture incidence was relatively higher in more deprived areas, particularly among men: IRR most vs least deprived quintile 2.06 (95% confidence interval [CI] = 2.00–2.12) in men, 1.62 (95% CI 1.60–1.65) in women. A relationship, albeit less marked, between deprivation and hip fracture incidence was observed among men in the Midlands and South, but with no clear pattern among women. Conclusions: Regional variation in hip fracture incidence exists across England, with the greatest absolute burden of incident hip fractures observed in the North East for both men and women. Across local areas in North England, absolute and relative inequalities in hip fracture incidence were greater than in other regions. Our findings highlight the need for improved fracture prevention programmes that aim to reduce regional and social inequalities in hip fracture incidence. Highlights: This is the first population-based study of inequalities in hip fracture incidence across geographic regions in England. We examined the effect of deprivation on hip fracture incidence using 14 years of data for 747, 369 hip fracture admissions. We determined that, after accounting for age, marked regional variation in hip fracture incidence exists across England. Absolute and relative inequalities in hip fracture incidence are greatest in the north of England. Our findings highlight the need for fracture prevention programmes aiming to reduce inequalities in hip fracture incidence.